Розв’яжіть рівняння: (2х + 1) + (3х + 2) + (4х + 3) = 5х + 10

Розв'яжіть рівняння: (2х + 1) + (3х + 2) + (4х + 3) = 5х + 10

  • (2х + 1) + (3х + 2) + (4х + 3) = 5х + 10
    2х + 1 + 3х + 2 + 4х + 3 = 5х + 10
    9х + 6 = 5х + 10
    9х-5х = 10-6
    4х = 4
    х = 1
  • 2x + 3x + 4x -5x = -6
    4x = -6
    x = -1,5

Понравилась статья? Поделись с друзьями:
Добавить комментарий

;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

37 + = 46